PELAKSANAAN SANKSI ADAT BAGI PELAKU ZINA DI NAGARI SURIAN KECAMATAN PANTAI CERMIN KABUPATEN SOLOK - Dori Handika; Elimartati Elimartati (JISRAH: Jurnal Integrasi Ilmu Syariah, 2023)
The main problem in this thesis is the Implementation of Traditional Sanctions for Adultery in Nagari Surian, Pantai Cermin District, Solok Regency and the aim is to find out and explain the Customary Sanctions for Adultery Actors in Nagari Surian, Pantai Cermin District, Solok Regency and to find out and analyze Islamic Law on customary sanctions for adultery. This type of research is Field Research field research. Data sources come from primary data sources, namely, Niniak Mamak, KUA, Youth Leader, Angku Kali, the community in Nagari Surian, Pantai Cermin District, Solok Regency. Secondary data sources are information and research location data. The data analysis technique used here is a qualitative descriptive analysis technique. As well as the data guarantor technique that is carried out is source triangulation. The result of the research is that the customary sanctions for adultery in Nagari Surian, Pantai Cermin sub-district, Solok regency, when someone commits adultery is caught by the community, the adulteress is brought to the Adat Nagari Density for trial, and is married off at the Nagari Adat Density, the adulteress is subject to a fine of one hundred sacks of cement and also a fine of one goat, this was agreed upon by Ninik Mamak and the surrounding community. After that, they brought the adulteress to the KUA office, officially married her and gave her a funeral. If you are fined or sanctioned in the form of being expelled from the village, you may return from the village again just to see your parents, you cannot stay from the village